Analysis of Factors Influencing Wage Levels for Informal Business Workers in the City of Mataram in 2022 - M. Firmansyah (LPPM Institut Studi Islam Sunan Doe, 2022)
This study examines the effect of age, working hours, education, gender on wage levels of informal business workers. Tests were carried out on 70 respondents spread across three sub-districts in the city of Mataram, namely Cakranegara, Sekarbela, and Ampenan sub-districts. This research is a quantitative-descriptive type. Determination of the sample was determined by purposive sampling, while the analysis used was descriptive analysis and SEM-PLS. The results indicate that working hours and gender have a positive and significant effect on the level of wages of formal business workers, while age and education have a positive but not significant effect. The findings indicate that a high number of working hours can have a direct effect on increasing workers' wages where the more hours a person works, the higher the wages received. Based on the results of the study, results were also found where the variables of education and age had a positive but not significant effect, indicating that workers/laborers who work in informal businesses determine the level of wages they get, not in terms of education and age of workers because in the informal business itself wage determination is seen from diligence and hard work done by the worker.